Upaya Pengurangan Waktu Proses Changeover Pada Mesin Fisher Pada Perusahaan Kemasan Kosmetik - Dhamma Prabha Dewa; I Nyoman Sutapa (Jurnal Titra, 2021)
The changeover time that occurred in one of the departments at companies had a pretty big time. Therefore, Improvements are needed in order to reduce the changeover time. The method that will be used to reduce the changeover time is by using the DMAIC method and assisted by the Single Minute Exchange of Dies (SMED) method. The study began by observing the machine that had the longest changeover time. The observations were carried out using the SMED method and analyzed using the SMED method as well. The results of the analysis will be a proposed Improvement for the machine in question. The results of the proposed Improvements are divided into two, some can be applied directly, and some cannot be applied directly due to certain conditions. Implementations that can be carried out directly will be observed and controlled so that they can run as expected, while those that cannot be carried out directly will only be in the form of ideas or prototypes as an illustration for the company.